2016
DOI: 10.4137/aci.s31614
|View full text |Cite
|
Sign up to set email alerts
|

Quality Issues of Research Antibodies

Abstract: According to several recent studies, an unexpectedly high number of landmark papers seem to be not reproducible by independent laboratories. Nontherapeutic antibodies used for research, diagnostic, food analytical, environmental, and other purposes play a significant role in this matter. Although some papers have been published offering suggestions to improve the situation, they do not seem to be comprehensive enough to cover the full complexity of this issue. In addition, no obvious improvements could be noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 53 publications
0
100
0
Order By: Relevance
“…The vendors are not still required to verify the quality of every new batch [49]. In an alerting notion Weller [20] hypothesized that high quality and well-characterized antibodies developed by academic groups are often sold to test kit manufacturers. Consequently, the antibodies available in the free market might be the ones with doubtful quality and insufficient information about their performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vendors are not still required to verify the quality of every new batch [49]. In an alerting notion Weller [20] hypothesized that high quality and well-characterized antibodies developed by academic groups are often sold to test kit manufacturers. Consequently, the antibodies available in the free market might be the ones with doubtful quality and insufficient information about their performance.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have addressed the issue and claimed for better characterization and profound information on the specificity and cross-reactivity of the antibodies [19][20][21][22][23][24][25][26][27][28]. The antibodies in the market are often insufficiently characterized and furthermore they might possess batch-to-batch variation, usually in much larger extent with polyclonal antibodies compared to monoclonal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In just one of the multiple studies on antibody reliability, the Human Protein Atlas examined over 5000 commercial antibodies and demonstrated that over 50% could not be used in the proposed application [2]. This has huge implications for research conducted using these antibodies.…”
Section: Even Stars Have Their Flawsmentioning
confidence: 99%
“…Since the 1970s when Köhler and Milstein produced hybridoma monoclonal antibodies (mAbs) through the fusion of antibody-producing mouse spleen cells with an immortal myeloma cell line [1], multiple research projects have utilized antibodies and it has been estimated that there are over 300 companies offering 2 million antibodies for research purposes [2]. …”
mentioning
confidence: 99%